Evaluation of HIV/AIDS patients' knowledge on antiretroviral drugs - Almeida,Regina Flávia de Castro (2009)
Lack of information on antiretroviral drugs or the misunderstanding of available information can facilitate incorrect use of such drugs. This can result in non-adherence to the prescribed regimen, leading to a great possibility of a therapeutic failure. The aim of this study was to know which information HIV/AIDS patients, who receive their medicines at the pharmacy of a reference hospital in the northeast Brazil, have on the drugs they use, the source of this information and whether there is a need for additional information. A total of 195 HIV/AIDS patients, who were using either zidovudina + lamivudina 300+150mg (AZT+3TC), efavirenz 600mg (EFZ) or lopinavir/ritonavir 133.33/33mg (LPV/r), were interviewed. The mean age was 41 years (SD = 9.55) and 70.8% were males. Of the total, 55.4% didn't know the effect of the drug in the organism; 35.9% were unaware of the necessity of taking antiretroviral drugs for the rest of their lives; only 14.4% knew how to proceed when a dosage was missed; 22.1% said they could die and the same number of individuals believed in aggravation of the disease in case of treatment interruption. The majority, 68.2%, considered it very necessary to receive drug information. The results show that there is an apparent lack of general information among users of antiretroviral drugs, and at the same time a need for it. It is necessary that all professionals involved in the health care of the patients agree that an efficient supply of information on prescribed drugs is an ethical component of the treatment that favors and fosters its adherence.